India in the Muslim Imagination: Cartography and Landscape in 19th Century Urdu Literature - Faisal Devji (South Asia Multidisciplinary Academic Journal)
The formation of the ‘Muslim community’ in colonial India necessitated a rethinking of the country itself in its physical and political geography. The Muslim modernists of North India who were gathered in the Aligarh Movement struggled both to assimilate themselves within the colonial cartography that was coming to define India as an idea, and, simultaneously, to inhabit it in distinctive new ways. Rather than serving to demonstrate the ‘incompletion’ of their modernity, this made for a narrative illustrating an epistemological ‘double consciousness’, of which this essay explores the Urdu literary tropes of the human figure, cartography, landscape and the ruin.